ANALISIS KOMPETENSI GURU PKn DALAM MENERAPAN KURIKULUM 2013 DI SMP NEGERI SEKECAMATAN STABAT - irfan dahnial (JURNAL TEMATIK, 2017)
This study aims to analyze the low competence of civic teachers in applying the Curriculum 2013at state junior high school of Stabat district. This study is a qualitative research. The subjects of this study were 16 civic teachers at state junior high school of Stabat district. The instruments were questionnaire, observation sheet, and interview guidelines. The results showed that: (1) The causes low competence of Civics teachers in applying the Curriculum 2013, that is: not all indicators on every competence with the good criteria, the facilites and infrastructure in applying the Curriculum 2013 at schools is not yet sufficient, and a making learning devices must reach many criteria so difficult for teachers to do; (2) How to overcome the low competence of Civics teachers in applying the Curriculum 2013, that is: to achieve four competencies conducted by training and improve indicators which not good criteria, conduct training or MGMP in order to make learning tools more appropriate with Civics education, socialization curriculum 2013 so the teachers better understand about Curriculum 2013, and need to improve the welfare of teachers, especially teachers who are non-civil servant status; and (3) The competencies most needed by Civics teachers in applying the Curriculum 2013 are professional competence or in Civics learning is civic disposition.